Nevus Spilus, Partial Unilateral Lentiginosis, and Linear and Whorled Nevoid Hypermelanosis: A Comparison of Clinical Features, Course, and Treatment Response - Hui-Ting Han; Jung-Je Park; Ji Su Lee; Si-Hyung Lee (Medical Journals Sweden, 2024)
Skin diseases manifesting as agminated pigmented lesions have overlapping clinical manifestations. Therefore, accurate differentiation is challenging. The clinical characteristics, histopathological findings, and treatment response of patients diagnosed with partial unilateral lentiginosis, nevus spilus, or linear and whorled nevoid hypermelanosis were retrospectively analysed. Each disease demonstrated distinct demographic and clinical characteristics, and the responses to laser treatment varied. The median age at onset varied significantly among the groups: 0.1, 6.6, and 0.5 years in patients with nevus spilus, partial unilateral lentiginosis, and linear and whorled nevoid hypermelanosis, respectively. Regarding the locations of the skin lesions, partial unilateral lentiginosis occurred predominantly on the head and neck, while approximately half of nevus spilus and linear and whorled nevoid hypermelanosis were observed on the extremities. Although linear and whorled nevoid hypermelanosis and partial unilateral lentiginosis share a similar histological feature of basal hyperpigmentation, patients with linear and whorled nevoid hypermelanosis showed the best response to laser treatment, while patients with partial unilateral lentiginosis demonstrated a poor treatment response. The study's data may provide important clues for the differential diagnosis and clinical decision-making regarding the treatment of these agminated pigmented lesions.